2011
DOI: 10.1002/tax.601016
|View full text |Cite
|
Sign up to set email alerts
|

A case study of DNA barcoding in Chinese Grimmiaceae and a moss recorded in China for the first time

Abstract: Mosses are among the basal lineages of embryophytes and one of the three bryophyte lineages. In the present study, four regions of chloroplast DNA (rbcL‐a, rps4, trnH‐psbA, trnL intron) were used to investigate the applicability of DNA barcoding to four moss genera of Grimmiaceae (Racomitrium, Coscinodon, Grimmia, Schistidium) in China. The species resolution of the four loci examined was 65% (trnH‐psbA), 59% (rps4), 53% (rbcL‐a) and 29% (trnL intron). However, rps4 (59%) provided a higher value of monophyleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The suitability of these markers for discriminating closely related moss species in species complexes, however, remained difficult to assess, as only few species from selected genera were compared. The subsequent study focusing on Grimmiaceae [9] already showed that (partial) rbcL sequences did not perform well, and the discrimination capacity of the best marker ( psbA- trnH ) did not exceed 65% in the whole family. In Racomitrium , all 11 species included in Liu et al [9] could be distinguished by rps4 , and with >80% success by rbcL and psbA-trnH , but again the question arises whether these markers would provide sufficient information when further closely related species are compared.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The suitability of these markers for discriminating closely related moss species in species complexes, however, remained difficult to assess, as only few species from selected genera were compared. The subsequent study focusing on Grimmiaceae [9] already showed that (partial) rbcL sequences did not perform well, and the discrimination capacity of the best marker ( psbA- trnH ) did not exceed 65% in the whole family. In Racomitrium , all 11 species included in Liu et al [9] could be distinguished by rps4 , and with >80% success by rbcL and psbA-trnH , but again the question arises whether these markers would provide sufficient information when further closely related species are compared.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pairwise nucleotide distances between all sequences were calculated according to the K2P model (cf. [8], [9]) for the combined dataset and all partitions, and compared between and within the species of the R. canescens complex.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The usefulness of DNA barcodes for bryophytes has also been proved, but this group of plants requires further testing (Rowntree et al, 2010;Crä utlein et al, 2011;Liu et al, 2011;Stech et al, 2011). Hence, alternative markers for species delimitation may be needed.…”
Section: Introductionmentioning
confidence: 99%